Attitudes of Consumers from the Sarajevo Canton in Bosnia and Herzegovina toward Advertising through Sport among the Question how Often they Participate in Sports Activities - Jovan Gardasevic; Izet Bajramovic; Bojan Masanovic (Journal of Anthropology of Sport and Physical Education)
Advertising is an attractive promotional tool for marketers who can use it to strengthen communication with consumers and persuade them to purchasing certain product or service. Hence, there is necessity to analyse their general attitudes among various questions, while this research was aimed at gaining relevant knowledge about the attitudes of Sarajevo consumers toward advertising through sport among the question how often they participate in sports activities. The sample included 358 respondents, divided into six subsample groups: consumers who do not participate in sport activities at all, then consumers who participate in sport activities less than ones a month, next 1–4 a month, 5–10 a month, 11–20 a month, as well as consumers participate in sport activities more than 20 times a month. The sample of variables contained the system of three general attitudes which were modelled by seven-point Likert scale. The results of the measuring were analysed by multivariate analysis (MANOVA) and univariate analysis (ANOVA) and Post Hoc test. Based on the statistical analyses it was found that significant differences occur at multivariate level, as well as between all three variables at a significance level of p=.000. Hence, it is interesting to highlight that it was found there are significant differences showed up between the consumers who participate in various sports activities. These results are so important for the marketers, mostly due to the reason they can’t merge all the potential consumers who participate in various sports activities into one homogeneous group. This is the case in previous investigations and this observation presents relevant information.